Andrew Claydon PhD - Gill, Philip; Claydon, Andrew; Gaulter, Sally; Kister, Guillaume (Cranfield University, 2020)
Current Polymer Bonded Explosive (PBX) formulation is limited by a compromise - optimised final properties against processability. While explosive content would ideally be maximised and plasticiser content ideally minimised, the formulation would become too viscous to cast and require arduous mixing processes using conventional techniques. However, with Resonant Acoustic Mixing (RAM), formulation does not have to be constrained. Instead of mixing blades, mixing is achieved using an oscillating platform to impart acoustic pressure waves (vibrations) into the mixture. Mixing is orders of magnitude faster than conventionally achievable, and the added ability to mix in the end use casing (mixing ‘in-situ’) also renders casting obsolete in many scenarios. The research aim of the PhD is to assess how machine control and vessel design can be altered to optimise the mixing mechanism and compare material properties of composites mixed ‘in-situ’ and ‘mixed and cast’.
Keywords: 'Explosives'; 'PBX'; 'Polymer Bonded Explosives'; 'Resonant acoustic mixing'; 'RAM'; 'Formulation'; 'Chemical Thermodynamics and Energetics'